Research on collaborative control method of positioning of operators and hydraulic support for coal mine fully-mechanized mining face - Zhanze LIANG; Shu ZHOU; Haijian CHEN (Meikuang Anquan, 2024)
In order to further improve the safety of coal mine comprehensive mining operations, a set of coal mine comprehensive mining personnel positioning and hydraulic support system control system is proposed with intelligent technology as the starting point; by designing a precise positioning system, dividing the control area of the coal mining face, and integrating the design system, an intelligent and automated coal mine comprehensive mining face working system was ultimately constructed. The application of collaborative control system in Daliuta Coal Mine shows that the system has strong safety and high stability, and can effectively ensure the life safety of coal mine comprehensive mining face operators.